Study of the Relationship Between the Acoustic Threshold and Threshold of Octave Masking - A, Jagadish (Journal of All India Institute of Speech and Hearing)
The value of the test battery approach in assessing human auditory function has been recognized for many years and may prove a more reliable approach to susceptibility testing. If several correlates were identified, they could be used as a test battery for susceptibility to noise-induced hearing loss. Psycho-acoustic tasks could be used as a new indices of susceptibility to noise-induced hearing loss, replacing traditional TTS-based susceptibility tests. The identification of psychoacoustic correlates of TTS may also provide new information about th e areas of the auditory system involved in the fatigue process and it may also be useful in detecting minimal auditory dysfunction. (Eldrege and Miller 1969, Ward and Durall 1971, Lipscomb, 1975).